2010
DOI: 10.1007/s12519-011-0245-0
|View full text |Cite
|
Sign up to set email alerts
|

Steroid response in moderate to severe pediatric ulcerative colitis: a single center’s experience

Abstract: approximately half of the pediatric patients had complete response to steroid therapy in a long period. PUCAS could be used as a potential marker of "failed response" to steroid, but should be supported with a number of prospective randomized controlled studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 13 publications
0
9
0
3
Order By: Relevance
“…Studies of oral steroids for treating children with active UC report short term (1-3 months) remission rates of 50-64% (108)(109)(110); at one year 49-61% had prolonged response, 14-49% were steroid-dependent and 5-29% required surgery (5,7,108,110). Mucosal healing lags behind clinical improvement; in a non-randomised study after 8 weeks of steroids or 5-ASA, 87% had clinical remission, 40% endoscopic remission and 15% histological remission with no significant difference in outcomes between the two therapies (111).…”
mentioning
confidence: 99%
“…Studies of oral steroids for treating children with active UC report short term (1-3 months) remission rates of 50-64% (108)(109)(110); at one year 49-61% had prolonged response, 14-49% were steroid-dependent and 5-29% required surgery (5,7,108,110). Mucosal healing lags behind clinical improvement; in a non-randomised study after 8 weeks of steroids or 5-ASA, 87% had clinical remission, 40% endoscopic remission and 15% histological remission with no significant difference in outcomes between the two therapies (111).…”
mentioning
confidence: 99%
“…PUCAI was developed for the noninvasive assessment of disease activity in patients with UC, and it was shown that it may be used for the prediction of steroid response. [30,31] Recently, a strong correlation was found between PUCAI and the likelihood of undergoing surgical procedure. [32] CRP and erythrocyte sedimentation rate were used in the diagnosis of UC, but the results were different.…”
Section: Original Articlementioning
confidence: 99%
“…In UC, systemic CS is an effective treatment of moderate‐to‐severe disease, including acute severe colitis (ASC). Reported short term remission rates (1–3 months) ranged from 50 to 64% 48–50 and 1‐year remission rates ranging from 49% to 61% 48–50 . However, a substantial proportion (14–49%) of children became steroid‐dependent by 1 year 48,49 …”
Section: Management Of Pediatric Ibd In Asiamentioning
confidence: 99%
“…Reported short term remission rates (1–3 months) ranged from 50 to 64% 48–50 and 1‐year remission rates ranging from 49% to 61% 48–50 . However, a substantial proportion (14–49%) of children became steroid‐dependent by 1 year 48,49 …”
Section: Management Of Pediatric Ibd In Asiamentioning
confidence: 99%